1979
DOI: 10.1364/ao.18.001490
|View full text |Cite
|
Sign up to set email alerts
|

Single-mode optical waveguides

Abstract: An efficient and powerful technique has been developed to treat the problem of wave propagation along arbitrarily shaped single-mode dielectric waveguides with inhomogeneous index variations in the cross-sectional plane. This technique is based on a modified finite-element method. Illustrative examples were given for the following guides: (a) the triangular fiber guide; (b) the elliptical fiber guide; (c) the single material fiber guide; (d) the rectangular fiber guide; guide; (g) the optical stripline guide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(42 citation statements)
references
References 15 publications
2
37
0
3
Order By: Relevance
“…5; convergence of the res ult has been confirmed by extending the section A1B1C1D1 in Fig. 4 to A2B2C2D2· When the present result is compared with the result of the vectorial finite-element method made by Yeh et al [9), good agreement is observed with a profile given by Eq. (4).…”
Section: Diffused Optical Waveguidesupporting
confidence: 75%
See 2 more Smart Citations
“…5; convergence of the res ult has been confirmed by extending the section A1B1C1D1 in Fig. 4 to A2B2C2D2· When the present result is compared with the result of the vectorial finite-element method made by Yeh et al [9), good agreement is observed with a profile given by Eq. (4).…”
Section: Diffused Optical Waveguidesupporting
confidence: 75%
“…On the other hand, the effect of a 2-dimensionally inhomogeneous refractive index profile [6] is considered in the treatments via the variational method [7], the effective index method [8], the finite element method [9], and the linear segment layer approximation [10], in which, however, the metal cladding and the dielectric overlay are not considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Goell [17] presented his circular harmonic computer analysis. Other approaches such as Knox and Toulios' [18] equivalent-index method, Yeh's [19] finite-element method, and Jain's [20] variational method have appeared later to solve the problem in different ways. However, all these techniques above analyze modes by a physical-optics method, which involves complex algebraic or differential calculation but does not give an explicit solution for the single mode condition of rectangular dielectric waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…This method is very accurate but time consuming. Another accurate method is the finite element method [4], but this requires computations involving large matrices, which is also time consuming. Garlerkin's method has been used with trigonometric [5] and Hermite-Gauss basis functions [6] to transform the scalar wave equation into a linear eigenvalue matrix equation.…”
Section: Introductionmentioning
confidence: 99%